Movement Patterns and Habitat Suitability of Translocated Sumatran Tigers (Panthera tigris sumatrae) - Farhan Reza Pahlevi; Lilik Budi Prasetyo; Dolly Priatna (Journal of Natural Resources and Environmental Management)
Sumatran tigers (Panthera tigris sumatrae), critically endangered mammals native to Indonesia, play a vital role in maintaining ecosystem balance by regulating prey populations. However, habitat loss and human-wildlife conflict necessitate translocation as a conservation strategy. Translocation becomes an option when the conflict site is no longer possible as a tiger habitat, and the landscape changes from homogeneous to heterogeneous, causing changes in biodiversity that impact resource changes. Ecological studies on the aspects of space use and suitability characteristics of habitats by translocated tigers need to be conducted to improve survival. This study analyzed the home range and habitat suitability of translocated Sumatran tigers in Kerinci Seblat National Park (KSNP) using GPS collar data collected between June and September 2022. This research was conducted by developing a species distribution model using the Minimum Convex Polygon (MCP), fixed kernel (FK), and maximum entropy (Maxent) programs. The most active time used in moving by Sumatran tigers was in the morning of 06.00–08.59, MCP 492 km2, and FK 98.9 km2. The results of Maxent modelling obtained an average AUC value of 0.88, and the performance of this model was very good. The response shows how the prediction of the Sumatran Tiger's presence changes with each varying landscape value. The total edge contribution is dominant, with a proportion in this model of 35.5% and a Class area proportion of 27.5%.